Effect of toxin binders on immunity and aflatoxin M1 residues in milk in buffaloes - WAKADE, B A; INGOLE, S D; BHARUCHA, S V; NAGVEKAR, A S (The Indian Journal of Animal Sciences, 2019)
To investigate the effect of dietary toxin binders on AFM1 and immunity in buffaloes 48 Murrah buffaloes in same lactating phase were divided into 4 groups, viz. control (C), T1, T2 and T3 (toxin binder fed buffaloes) comprising of 12 animals each. The average milk AFM1 concentration decreased slightly in control group while marked decrease was found in T1 group throughout the experiment. The average milk SCC showed non significant increase in all the groups. Serum IgG concentration in control group decreased significantly from day 0 to day 45, while in groups T1, T2 and T3 there was significant increase, whereas no significant difference in serum IgG concentration was observed between the groups. The average serum total protein concentration in all the groups from day 7 through day 15, 30 and 45 was almost similar and within reference range. There was no significant difference between the groups. The average serum SGOT level was significant between the days in all the groups. The average SGPT concentration between the days was non significant in control and T1 groups and significant decrease was observed in T2 and T3 groups. The SGPT concentration was highly significant between control and T1, T2, T3 groups, respectively. The results suggested that feeding of toxin binder is effective in reducing AFM1 in milk at the dose rate of 50 mg/day having composition of exal 44.44% + bentonite 55.56% indicating that it provides a potential protective mechanism against aflatoxin exposure and also some alterations in biochemical parameters and IgG.